The Quality of Veterans Healthcare Administration Cardiovascular Care - D. Elizabeth Le, MD; Bhaskar L. Arora, MBBS; Faith R. Kelly, MD; Stephen W. Waldo, MD; Merritt Raitt, MD; Paul Heidenreich, MD, MS; Samit M. Shah, MD, PhD; Ali E. Denktas, MD; Kreton O. Mavromatis, MD (JACC: Advances)
A total of 9 million veterans receive care in a unique healthcare system, the Veterans Healthcare Administration (VHA), with nearly 50% reporting at least one cardiovascular disease. Despite evidence for high quality of health care in the VHA, more veteran care is being moved to the non-VHA community. An assumption of this shift in care is that the quality of non-VHA care is at least comparable to VHA care. This paper reviews the quality of cardiovascular care delivered by the VHA in comparison to community care, which is care delivered in non-VHA facilities by non-VHA providers and is authorized and paid for by VHA, examining quality metrics and highlighting novel national care programs. The critical examination of this data is valuable for deriving health care policy, sharing novel and effective quality initiatives throughout the healthcare sector, and will help veterans and their providers make important healthcare decisions.